31.4: Invited Paper: Long‐lifetime Blue Organic Light‐emitting Diode. (28th November 2018) - Tseng, Po-Chen; Lee, Ming-Zer; Hsieh, Julie; Chen, Stanley; Lee, Jiun-Haw
Abstract : 36% elongation of operation lifetime was achieved in a blue triplet‐triplet annihilation organic light‐emitting diode (TTA‐OLED) by using a new hole‐transporting layer (HTL) material, which exhibited suitable highest occupied molecular orbital (HOMO) level for hole‐injection, and had high hole‐mobility to improve carrier balance. Besides, it was robust against electron accumulation between the interface of the HTL and the emitting layer.